Pakistani prison libraries: an assessment of services and challenges. Issue 1 (5th December 2018) - Hussain, Tauseef; Batool, Syeda Hina; Soroya, Saira Hanif; Warraich, Nosheen Fatima
Abstract : Purpose: The purpose of the paper is to examine the current status of prison libraries, their role, services and collection in Pakistani context. It also attempts to highlight the main problems faced by selected libraries. Design/methodology/approach: The qualitative research approach was adopted to achieve the study objectives. Data were collected using face-to-face interviews to find out respondents' views about libraries in prison. Findings: Findings of the study confirmed that inmates' library queries are mostly related to the legal matters, and it is quite natural. One of the significant services of the Pakistani prison libraries is to help prisoners in their education. The main role of the library caretaker was to educate and offer rehabilitation programs. Unavailability of library space, lack of professional staff, limited collections, poor budgetary situation and censorship issues are the major challenges that Pakistani prison libraries are facing. Social implications: The study findings further implicate that open libraries and access to books would promote positivity within society and reduce criminal and immoral acts. Originality/value: It is the first of its kind and unique study that presents the current situation of prison libraries in the Pakistani context. The study has practical implications for policymakers to give importance to prison libraries in terms of finance, professional staff and the availability of information sources.